2020
DOI: 10.1029/2019jd030913
|View full text |Cite
|
Sign up to set email alerts
|

Ice Nucleation by Marine Aerosols Over the North Atlantic Ocean in Late Spring

Abstract: Here we report the ice nucleating temperatures of marine aerosols sampled in the subarctic Atlantic Ocean during a phytoplankton bloom. Ice nucleation measurements were conducted on primary aerosol samples and phytoplankton isolated from seawater samples. Primary marine aerosol samples produced by a specialized aerosol generator (the Sea Sweep) catalyzed droplet freezing at temperatures between −33.4 °C and − 24.5 °C, with a mean freezing temperature of −28.5 °C, which was significantly warmer than the homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 90 publications
(164 reference statements)
4
32
0
2
Order By: Relevance
“…Indeed, the ice nucleation activity of marine aerosol has been related to the organic content of SSA (DeMott et al, 2016; McCluskey, Hill, Humphries, et al, 2018; McCluskey, Hill, Sultana, et al, 2018; McCluskey, Ovadnevaite, Rinaldi, et al, 2018; Wilson et al, 2015), while no ice nucleation ability is attributed in literature to secondary (organic or inorganic) particles. Supporting our findings, a relation between algal blooming and ice nucleating properties of SSA has already been reported in the literature (McCluskey et al, 2017; Wilbourn et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the ice nucleation activity of marine aerosol has been related to the organic content of SSA (DeMott et al, 2016; McCluskey, Hill, Humphries, et al, 2018; McCluskey, Hill, Sultana, et al, 2018; McCluskey, Ovadnevaite, Rinaldi, et al, 2018; Wilson et al, 2015), while no ice nucleation ability is attributed in literature to secondary (organic or inorganic) particles. Supporting our findings, a relation between algal blooming and ice nucleating properties of SSA has already been reported in the literature (McCluskey et al, 2017; Wilbourn et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Our results augment previous findings that particle composition determines the ice nucleation activity of SSA (DeMott et al, 2016;McCluskey et al, 2017;Wilbourn et al, 2020;Wilson et al, 2012;Wolf et al, 2019). We also found that INP activity is uncorrelated with variables like nutrient concentration, wind speed, and chlorophyll concentration (Table S2 in the Supplement).…”
Section: Atmospheric Implicationssupporting
confidence: 90%
“…Note that this upper limit of the ice nucleation activity of the field samples, however, is still 1 order of magnitude lower than the n s parameterization for mineral dust (Fig. 5, Niemand et al, 2012), underlining the relatively poor heterogeneous ice nucleation activity of sea spray aerosol particles compared to other atmospherically relevant types of INPs in the temperature range above 248 K. In the (high) Arctic, both transported dust and sea spray aerosol (transported or local) can be present (see Willis et al, 2018, for a thorough review of literature). However, which source is dominant for ice nucleation might be locally very different.…”
Section: Temperature Regime Below 248 K (Aerosolized Samples)mentioning
confidence: 85%